Identification of Core Allosteric Networks and Development of QSAR Models for EPAC1 - Mohamed, Hebatallah (My University, 2021)
Allosteric regulation is essential to control biological function. In addition, allosteric sites offer a promising venue for selective drug targeting. However, accurate mapping of allosteric sites remains challenging since allostery relies on often subtle, yet functionally relevant, structural, and dynamical changes. In this thesis, a new toolset of NMR-based methodologies known as T-CHESCA and CLASS-CHESCA are proposed to identify key allosteric sites, using isoform 1 of the exchange protein activated by cAMP (EPAC1) as the model system. The T-CHESCA imposes changes on the fast-exchanging active/inactive states of the protein through temperature changes while the CLASS-CHESCA imposes changes through variations in the spin-active nuclei involved in pairwise correlations of residues. The residue ensembles identified by the CHESCA methods were found in previously identified EPAC allosteric sites. EPAC1 has also been identified as a promising drug target for cardiovascular diseases and based on structural analogues of a novel EPAC1-specific inhibitor called I942, the next aim of the work was to generate a quantitative structure activity relationship model (QSAR). The QSAR model was able to predict the affinity of a promising inhibitor with enhanced potency and inhibitory activity compared to I942 which was confirmed through competition assays, 15N-1H HSQC experiments, saturation transfer difference (STD) and chemical shift projection analysis (CHESPA).